O papel do RH sob a percepção da alta direção e a do gestor de RH comparado à perspectiva teórica atual - Maffei, Paulo Antonio de Jesus (2005)
The purpose of this study is to identify, compare and analyze the perceptions of Presidents of companies and HR Managers under the role of the Human Resources area, in a limited group of eleven national and multinational companies, located in the Capital of the State of São Paulo. Initially, starting from the bibliographic research of specialized authors in the Human Resources area, a theoretic, conceptual master line was drawn, identifying the three main HR roles mentioned in the bibliography, namely: the HR acting as Strategic Partner (SP), as Operational Support area (OS) and as Change Agent (CA). This master line was utilized as a reference point for the analyzes which followed. In order to obtain the data, a questionnaire was developed with twenty-one queries sent out to the eleven Presidents of Companies selected in the sample and to their respective HR Managers, summing up twenty-two respondents. It was found that there are important differences between the theoretical perspective concerning the HR role and the reality found in the eleven researched companies from the perception of their Presidents and HR Managers. The roles of Strategic Partner (SP) and Changing Agent (CA) showed the greatest divergences among the persons surveyed, this is, Presidents have quite a different perception concerning their HRs in relation to the Strategic Partner and Changing Agent roles, when compared to their respective Human Resources Managers. On the other hand, a larger convergence level was identified among the two groups in relation to the Operational Support role (OS), where the difference in punctuation marks was much smaller. These results opened space for recommendations, with the purpose of reducing the gaps identified among the Presidents and HR Managers of these eleven surveyed companies.